Cape Verde : Fifth Review Under the Policy Support Instrument; Staff Report; Staff Supplement; Press Release on the Executive Board Discussion; and Statement by the Executive Director for Cape Verde. (IMF Staff Country Reports; Country Report ;, 2009)
This paper presents key findings of the Fifth Review under the Policy Support Instrument for Cape Verde. All quantitative assessment criteria for end-June 2008 were met. GDP growth remains generally resilient, and inflation pressures have been contained. Progress on structural measures has been steady despite delays on many measures. The authorities have scope to manage the external shocks because over the last few years, they have made faster-than-planned progress in both increasing international reserves and reducing domestic debt.